Pengaruh Peningkatan Temperatur Karbonisasi Terhadap Karakteristik Struktur Pori Pada Bambu Betung - Romualdo Winner Napitu, Jeremia; Winaya, I Nyoman Suprapta; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract In an effort to get a level of comfort, a compressor-based air conditioning (AC) system is used that requires a very large amount of electrical energy and can increase global warming. Therefore, a more energy efficient and environmentally friendly cooling system is needed. One such alternative cooling system is direct evaporative cooling system. In direct evaporative cooling system, cooling effect is given by evaporation process that occurs in pad material that has been moistened by water. The pad material itself is used for evaporative cooling system application, as cooling media. This study aims to analyze the effect of increasing carbonization temperature on pore structure characteristics, porosity and fluid surface tension in betung bamboo. As a raw material, bamboo can produce porous charcoal with a high spesific surface area and high porosity. Used carbonization temperatures of 500ºC (T1), 600ºC (T2), 700ºC (T3), and 800ºC (T4). The results of all tests indicate that the T4 specimen (800ºC) has a very large potential to be used as a new pad material in the direct evaporative cooling system. With the following characteristics: the T4 specimen has a pore radius of 36.97 ?m with a total of 134 pores and is relatively more homogeneous. Keywords: Direct evaporative cooling, betung bamboo, carbonization, and pore structure.